Angular distributions of multiply charged fragments from dissociation of Nitrogen molecules by Xe9+ impact. (July 2015) - Kumar, Ajit; Sairam, T; Rajput, Jyoti; Nair, Lekha; Safvan, C P
Synopsis: The angular distribution of the correlated molecular fragments with respect to the incoming beam direction for several of dissociation channels of multiply charged N2 molecule on collision with Xe 9+ was studied.